Niger : The Natural Resources Management Project - Mohan, P. C. (2012)
The Natural Resources Management Project (1996-2002), was intended to provide assistance to the Government of Niger to (a) assist rural communities in designing and implementing community-based land management plans by providing them with the necessary know-how, information, technical and financial resources, and proper institutional and legal framework for implementation; and (b) assist the Borrower in building capacity to promote, assist and coordinate various natural resources management initiatives within the framework of a long term national program. Project design capitalized on experience gained in Niger and the sub-region by the Bank and other donors (multilateral and bilateral) in community-based operations and natural resources management. During the first phase (1996-1999), efforts focused on capacity building at both Institutional and community level, and by January 2000, when the MTR was implemented, the 95 communities originally targeted for implementation had drafted their community development plans including CBNRM (Community-Based Natural Resources Management). An episode of acute food crisis in 1998 resulted in these plans focusing initially on food security and the establishment of community cereal banks. At the Mid term Review (January 2000), community based procurement was introduced, and implementation was extended to a further 30 communities bringing the total number of beneficiaries to half a million.